Making Your Home a Shelter: Electronic Monitoring and Victim Re-entry in Domestic Violence Cases - Erez, Edna (The British journal of criminology, 2007)
The development of bilateral electronic monitoring BEM exemplifies how shifts in the "culture of control" Garland, 2001, including a focus on domestic violence DV victims' emotional welfare and integration into proceedings, can alter abused partners' everyday lives. As a protective strategy, BEM provides DV victims with an alternative to relocating to a shelter. The subjective sense of safety engendered by program involvement emerges gradually, as everyday environments are re-evaluated in light of an estranged partner's absence; through social interactions with family members, friends, and justice agents; and as the understanding of what it means to be "protected" develops. The use of BEM technology to promote victim welfare rather than as a strictly evidentiary tool suggests that this expression of the new paradigm of justice is oriented toward victim re-entry into civil society